TRABALHO ESCRAVO CONTEMPORÂNEO: VIOLAÇÃO AO PRINCÍPIO DA DIGNIDADE DA PESSOA HUMANA - Carla Sendon Ameijeiras Veloso (TRF2, 2020)
The present work presented a brief summary of the history of how slavery was rooted around the world, presenting the main impacts to the victims. The study began with the emergence of slavery in Brazil, after the discovery of the country, by strengthening the practice with Indians, then the blacks and, more recently, the most vulnerable populations, regardless of race, with the so-called contemporary slave labor. An activity that has caused enormous damage to human dignity, as has also emphasized this article and that until today, no law nor public policies have managed to completely bar.